América Latina : militarismo 1940-1975 / Jaime Pinzón López, Reynaldo Muǫz Cabrera ; prólogo de Guillermo Cano Isaza - Muǫz Cabrera, ReynaldoCano, Guillermo (1925-1986); Pinzón López, Jaime (Serie monográfica de Ciencias Sociales y Políticas de la Fundación Friedrich Naumann)
Bibliografía